Wetlands and global warming: impacts, adaptation and mitigation (Developing Countries' Perspective) - Ansari, Abdul Haseeb; Oseni, Umar Aimhanosi (Serials Publication, 2012)
Wetlands are important components of the environment which equally benefit the environment and the people socially and economically depending on them. If wetlands are degraded or lost, there might be irreversible damage to the environment, and people depending on them might suffer from economic setback. The importance of wetlands received an added importance after the tsunamis which caused excessive damage due to dilapidated conditions of coastal wetlands. Global warming has its synergies with wetlands as their drainage, degradation and mismanagement can emit relatively more greenhouse gases into the atmosphere.